Answer to Question #211671 in Differential Equations for Bilal Ur Rehman

Question #211671

In the following problem use a suitable substitution to reduce the order of the given DE and then solve it


  1. y''=2y'
  2. y''+eyy'2=0
  3. y"+(1-1/y)y'2=0
1
Expert's answer
2021-06-30T12:34:56-0400
  1. y''=2y'

Substitution: "y' = p(y) \\Rightarrow y'' = p\\frac{{dp}}{{dy}}"

Then

"p\\frac{{dp}}{{dy}} = 2p \\Rightarrow \\frac{{dp}}{{dy}} = 2 \\Rightarrow dp = 2dy \\Rightarrow p = 2y + 2{C_1} \\Rightarrow \\frac{{dy}}{{dx}} = 2y + 2{C_1} \\Rightarrow \\frac{{dy}}{{y + {C_1}}} = 2dx \\Rightarrow \\ln |y + {C_1}| = 2x - 2{C_2} \\Rightarrow 2x = \\ln |y + {C_1}| + 2{C_2} \\Rightarrow x = \\frac{1}{2}\\ln |y + {C_1}| + {C_2}"

Answer: "x = \\frac{1}{2}\\ln |y + {C_1}| + {C_2}"

2.. y''+eyy'2=0

Substitution: "y' = p(y) \\Rightarrow y'' = p\\frac{{dp}}{{dy}}"

Then

"p\\frac{{dp}}{{dy}} + {e^y}{p^2} = 0 \\Rightarrow p\\frac{{dp}}{{dy}} = - {e^y}{p^2} \\Rightarrow \\frac{{dp}}{{dy}} = - {e^y}p \\Rightarrow \\frac{{dp}}{p} = - {e^y}dy \\Rightarrow \\ln p = - {e^y} + C \\Rightarrow p = {e^{ - {e^y} + C}} \\Rightarrow y' = {C_1}{e^{ - {e^y}}},\\,\\,{C_1} = {e^C} \\Rightarrow \\frac{{dy}}{{dx}} = {C_1}{e^{ - {e^y}}} \\Rightarrow \\frac{1}{{{C_1}}}{e^{{e^y}}}dy = dx \\Rightarrow x = \\frac{1}{{{C_1}}}\\int {{e^{{e^y}}}dy} + {C_2} \\Rightarrow x = \\frac{1}{{{C_1}}}Ei({e^y}) + {C_2}"

Answer: "x = \\frac{1}{{{C_1}}}Ei({e^y}) + {C_2}"

3.. y"+(1-1/y)y'2=0

Substitution: "y' = p(y) \\Rightarrow y'' = p\\frac{{dp}}{{dy}}"

Then

"p\\frac{{dp}}{{dy}} + \\left( {1 - \\frac{1}{y}} \\right){p^2} = 0 \\Rightarrow p\\frac{{dp}}{{dy}} = - \\left( {1 - \\frac{1}{y}} \\right){p^2} \\Rightarrow \\frac{{dp}}{{dy}} = \\left( {\\frac{1}{y} - 1} \\right)p \\Rightarrow \\frac{{dp}}{p} = \\left( {\\frac{1}{y} - 1} \\right)dy \\Rightarrow \\ln p = \\ln y - y + C \\Rightarrow p = {e^{\\ln y - y + C}} \\Rightarrow p = {C_1}{e^{\\ln y}}{e^{ - y}},\\,\\,{C_1} = {e^C} \\Rightarrow y' = {C_1}y{e^{ - y}} \\Rightarrow \\frac{{dy}}{{dx}} = {C_1}y{e^{ - y}} \\Rightarrow \\frac{1}{{{C_1}}}\\frac{{{e^y}dy}}{y} = dx \\Rightarrow x = \\frac{1}{{{C_1}}}\\int {\\frac{{{e^y}dy}}{y}} + {C_2} \\Rightarrow x = \\frac{1}{{{C_1}}}Ei(y) + {C_2}"

Answer: "x = \\frac{1}{{{C_1}}}Ei(y) + {C_2}"



Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog